Modeling Fluid-Structure Interaction in Cavitation Erosion: Preliminary Results. (November 2015) - Paquette, Yves; Pellone, Christian; Fivel, Marc; Ghigliotti, Giovanni; Johnsen, Eric; Franc, Jean-Pierre
Abstract: This paper is devoted to cavitation erosion modeling. It presents some recent numerical developments made in the code initially developed in collaboration with E.Johnsen and collaborators at University of Michigan [1] in order to account for fluid-structure interaction. The considered test case is that of a single air bubble collapsing near a wall due to an incident shock wave in the surrounding water. In our investigation, we focus on the code implementation and optimization and the bubble implosion mechanism. The paper is focused on the various events occurring during bubble collapse and the computation of the time evolution of the pressure distribution. The influence of the amplitude of the incident wave and the distance of the bubble to the wall are investigated.